2014
DOI: 10.1021/ol502964s
|View full text |Cite
|
Sign up to set email alerts
|

Chlorocatechelins A and B from Streptomyces sp.: New Siderophores Containing Chlorinated Catecholate Groups and an Acylguanidine Structure

Abstract: Two novel siderophores, chlorocatechelins A and B, were isolated from a culture broth of Streptomyces sp. Their structures were determined by spectroscopic analysis and degradation study. They contain chloro-substituted catecholate that has not been reported in natural products, whereas this group was conjugated to guanidine to form acylguanidine in chlorocatechelin A. This acylguanidine decomposed in weakly acidic solutions to furnish a less potent siderophore chlorocatechelin B. Chemical and biological insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…In the previous study, we noticed that compound 1 decomposed under acidic conditions; hence, protecting groups needed to be cleaved under neutral or basic conditions. 5 We chose benzyl groups for protecting all of the hydroxyl groups. The left segment 4 could be obtained by conjugating two molecules of benzyl-protected CDB 6 and one molecule of D-Arg (7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, we noticed that compound 1 decomposed under acidic conditions; hence, protecting groups needed to be cleaved under neutral or basic conditions. 5 We chose benzyl groups for protecting all of the hydroxyl groups. The left segment 4 could be obtained by conjugating two molecules of benzyl-protected CDB 6 and one molecule of D-Arg (7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Their structures were determined by spectroscopic analyses and degradation study. 5 Chlorocatechelin A (1) represents a characteristic structure; it contains two units of 4-chloro-2,3-dihydroxybenzoic acid (CDB), which has never been reported in natural products, and one unit of CDB is condensed with guanidine to form an acylguanidine. The acylguanidine is rarely found in natural products; 6−8 rare examples are Rhodococcus-derived siderophores, heterobactin A (3), and its derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[47] However,d ue to the fact that Fe III is almost insoluble and Fe II is unstable and highly toxic to cells, environmental iron is not easily taken up and utilized by microorganisms. [49] In addition to the fact that they were the first natural products that contain chloro-substituted catecholate,c hlorocatechelin Ap ossesses ar are acylguanidine moiety.T heir antimicrobial activities toward desferrioxamine B-sensitive microbes (such as Pasteurella piscicida) [50] indicatet hat chlorocatechelins may act as species-specific siderophores similart oa mychelin [51] and frustrate "siderophore piracy"byn eighboringb acteria. [48] Previously,w ed iscovered two unique siderophores,c hlorocatechelins Aa nd Bf rom Streptomyces sp.…”
Section: Siderophores As Molecular Tools For Resource Competitionmentioning
confidence: 99%
“…ML93-86F2. [49] In addition to the fact that they were the first natural products that contain chloro-substituted catecholate,c hlorocatechelin Ap ossesses ar are acylguanidine moiety.T heir antimicrobial activities toward desferrioxamine B-sensitive microbes (such as Pasteurella piscicida) [50] indicatet hat chlorocatechelins may act as species-specific siderophores similart oa mychelin [51] and frustrate "siderophore piracy"byn eighboringb acteria. [52] As ac lassic case study of competition for iron between microbes, Traxler et al reported the diverse production of actinobacterials iderophores triggered by interspecies interactions (Scheme 5).…”
Section: Siderophores As Molecular Tools For Resource Competitionmentioning
confidence: 99%
“…Two siderophores, chlorocatechelins A and B, with 4-chloro-2,3-dihydroxybenzoic acid [111], were isolated from a culture broth of Streptomyces sp. Both contained chloro-substituted catecholate that has not been reported in natural products; this group was further conjugated with guanidine to form acylguanidine in chlorocatechelin A (Kishimoto et al, 2014). Ariakemicins A and B, unusual linear hybrid polyketidenonribosomal peptide antibiotics, were discovered in the fermentation extract of marine Rapidithrix sp.…”
Section: Aromatic Fatty Acidsmentioning
confidence: 99%